Pengetahuan Ibu Tentang Pemberian Vitamin A Pada Ibu Nifas Dan Peran Bidan Dalam Pencapaiannya Di Puskesmas Rambah Samo I Tahun 2019 - Irayanti, Ermiza, (Jurnal Martenity and Neonatal, 2019)
The benefits of vitaminÂ A in addition to increase the immune system and help the recovery of maternal health parturition are closely related with anemia and reduce the risk night blind on nursing mother.The provision of the capsule was first, soon after giving birth and the capsule second given at least one day after the provision of the capsule first and no more than 6. weeks later. The puerperium is the time following the ratification of the placenta until the tools - reproductive tool good as before pregnant and normally the puerperium Â lasted for 6 weeks or 40 days. The puerperium is crucial to in order to lower in not maternal and infant mortality rate in indonesia, vitamin A deficiency could increase the risk the against an onset infection as diseases of the breath and diarrhea, increase the death by measles, and cause delays in growth. The purpose of this research to knowing knowledge mommy about the vitamin A on the number and role of midwives in parturition at puskesmas rambah samo 1 year 2019. Research methodology used is desktriptif with the design method used the cross sectional.The results obtained the majority of respondents having lacking knowledge about the 73 ( 96,1 % ) and obtained the midwife role in the vitamin a as many as people ( 43 56,6 % ).